Nisin and ε-polylysine combined treatment enhances quality of fresh-cut jackfruit at refrigerated storage - Zeng, Liping; Fan, Aiping; Yang, Guangming; Nong, Yuping; Lu, Yifan; Yang, Ruopeng (Frontiers in Nutrition, 2024)
This study investigated the effects of nisin combined with ε-polylysine on microorganisms and the refrigerated quality of fresh-cut jackfruit. After being treated with distilled water (control), nisin (0.5 g/L), ε-polylysine (0.5 g/L), and the combination of nisin (0.1 g/L) and ε-polylysine (0.4 g/L), microporous modified atmosphere packaging (MMAP) was carried out and stored at 10 ± 1 ℃ for 8 days. The microorganisms and physicochemical indexes were measured every 2 days during storage. The results indicated that combined treatment (0.1 g/L nisin, 0.4 g/L εpolylysine) had the best preservation on fresh-cut jackfruit. Compared with the control, combined treatment inhibited microbial growth (total bacterial count, mold and yeast), reduced the weight loss rate, respiratory intensity, polyphenol oxidase and peroxidase activities, and maintained higher sugar acid content, firmness, and color. Furthermore, it preserved higher levels of antioxidant compounds, reduced the accumulation of malondialdehyde and hydrogen peroxide, thereby reducing oxidative damage and maintaining high nutritional and sensory qualities. As a safe application of natural preservatives, nisin combined with ε-polylysine treatment has great application potential in the fresh-cut jackfruit industry.